Endoscopic Endonasal Surgery for Resection of Giant Craniopharyngioma in a Toddler—Multimodal Presurgical Planning, Surgical Technique, and Management of Complications: 2-Dimensional Operative Video. Issue 1 (9th December 2019) - Fernandez-Miranda, Juan C; Hwang, Peter; Grant, Gerald
Abstract: A 2-yr-old patient with a giant craniopharyngioma presented with seizures and panhypopituitarism. The lesion was initially approached at an outside institution with a transfrontal cyst fenestration, but progressive growth occurred later. Multiple management options were considered; we recommended an endoscopic endonasal approach with the goal of maximal safe resection. Virtual reality simulation and 3-dimensional printing were employed to evaluate whether the absence of pneumatization of the sinuses and the overall size of the nasal cavity could preclude effective surgical access. Our lab results suggested the binostril approach was feasible. A wide surgical exposure was performed from planum sphenoidale to clivus and from orbit to orbit. After removing the large calcified tumor portion, we found an accurate plane of dissection between tumor capsule, hypothalami, and visual pathways. By the end of resection, arterial bleeding was encountered secondary to an avulsion of the posterior communicating artery from the posterior cerebral artery. An angled aneurysm clip was placed with a single-shaft applier to secure the site of injury without narrowing the parent artery. Immediate and delayed magnetic resonance imaging and computed tomography angiography studies showed gross total resection, no stroke, and no pseudoaneurysm formation. On postoperative day 9, patient developed neurological decline and pneumocephalus secondary to necrotic nasoseptal flap. Two endonasal repairs with a lateral nasal wall flap were attempted with no success. A temporoparietal fascia flap was then harvested and transposed from the temporal to the pterygopalatine fossa to successfully repair the skull base defect. The patient has made an extraordinary recovery with no neurological sequalae. The patient's parents provided consent for the procedure and use of intraoperative photos and videos for academic purposes. Institutional Review Board approval was not required.